Cyclic performance of cross restrained steel plate shear walls with transverse braces - Yu, Jin-Guang; Feng, Xiao-Tian; Li, Bo; Hao, Ji-Ping (Elsevier, 2018)
This paper presents an investigation on the cyclic performance of cross restrained steel plate shear walls (SPSWs) with transverse braces. Transverse braces connecting to two columns are proposed to replace horizontal cross stiffeners on the infill steel plates. Effects of transverse braces on the performance of SPSWs are estimated through an experimental study and a finite element analysis. Two 1/3-scale two-story single-bay SPSW specimens, including one unstiffened SPSW and one cross restrained SPSW with transverse braces, are first tested under the quasi-static cyclic loading. Subsequently, finite element models for SPSWs are developed and verified by the test results. Cyclic performance of SPSW structures with different restrains for the infill steel plates are compared in terms of failure mode, loading capacity, energy dissipation capacity and stiffness degradation. Emphasis is given on the stress development and out-of-plane deformation of infill steel plates. The results show that use of transverse braces as the substitute of horizontal stiffeners enhances the loading capacity, energy dissipation capacity and ductility of SPSW structure. It is also effective to homogenize stress distribution and to restrain the out-of-plane deformation of infill steel plates, which finally decreases the additional bending moments applied to the columns. Compared with the unstiffened SPSWs, the maximum inward flexural deformation of columns in the cross restrained SPSWs with transverse braces is reduced by about 40.0%. It has demonstrated that the proposed cross restrainers combined with transverse braces are effective in improving the cyclic performance of SPSWs.